2020
DOI: 10.3389/fphar.2020.570776
|View full text |Cite|
|
Sign up to set email alerts
|

The Mechanism of Aureusidin in Suppressing Inflammatory Response in Acute Liver Injury by Regulating MD2

Abstract: ObjectiveIn this study, we mainly explored the mechanism and target of the anti-inflammatory effects of Aureusidin (Aur) in acute liver injury.MethodsLipopolysaccharide (LPS) was used to induce inflammatory injury in Kupffer cells (KCs) in vitro. After Aur treatment with gradient concentration, flow cytometry, propidium iodide (PI) staining, and Hoechst 33342 staining were used to detect the apoptotic level of KCs, and an enzyme-linked immunosorbent assay (ELISA) was used to detect the expression levels of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The animals were raised according to the National Health Guidelines for the Care and Use of Laboratory Animals. ALF model was performed as described previously with minor alteration [ 8 ]. To determine a suitable dose for the next experiment, mice were divided into 5 groups ( n = 6 to 12/per group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were raised according to the National Health Guidelines for the Care and Use of Laboratory Animals. ALF model was performed as described previously with minor alteration [ 8 ]. To determine a suitable dose for the next experiment, mice were divided into 5 groups ( n = 6 to 12/per group).…”
Section: Methodsmentioning
confidence: 99%
“…D-Galactosamine (D-GalN) is a hexosamine derived from galactose which can cause hepatic damage [ 7 ]. LPS and D-GalN can lead to hepatic injury in the mouse, which is similar to fulminant hepatic failure in clinic [ 8 ]. Therefore, a LPS/D-GalN-induced hepatic injury model has been widely used to explore potential hepatoprotective medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of MD2 level can inhibit the activation of TLR4 signalling and inhibit mucosal barrier damage caused by inflammation. Additionally, our previous study has also demonstrated that aureusidin is an effective inhibitor of MD2 to suppress inflammation 14 . In this study, we modified the structure of aureusidin and found that CNQX had anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 81%
“…The preliminary study of our group has found that aureusidin is a small molecule targeting MD2 through screening and research. Through liver injury models, pull‐down and immunoprecipitation assays have shown that aureusidin can inhibit the activation of TLR4/MD2‐NF‐κB by binding to the MD2 protein 14 . Further structural modification identified that an open‐loop derivative CNQX exerted a significant anti‐inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%
“…This molecule, which rarely occurs in nature, was previously isolated from mosses marine brown algae and flowering plants [ 24 , 25 ]. Aureusidin possesses a pharmacological profile showing high antioxidant and lipoxygenase inhibitory activity [ 26 ], as well as anti-inflammatory effects [ 27 , 28 ]. Luteolin ( 7 ), a flavone, which is abundant in edible plants, displays a wide range of biological activities including antioxidant, anti-carcinogenic [ 29 ], cardioprotective [ 30 ], anti-inflammatory, and antipruritic [ 31 ] activities.…”
Section: Resultsmentioning
confidence: 99%